Celebrating J.N. Findlay"s contribution to philosophy: A comparative textual analysis from a Mahāyāna Buddhist perspective - Mason, Garth J. (HTS teologiese studies, 2022)
J.N. Findlay was a South African philosopher who published from the late 1940s into the 1980s. He had a prestigious international academic career, holding many academic posts around the world. This article uses a textual comparative approach and focuses on Findlay’s Gifford Lecture at St Andrews University between 1965 and 1970. The objective of the article is to highlight the extent to which Findlay’s philosophical writings were influenced by Mahāyāna Buddhism. Although predominantly a Platonist, Findlay drew influence from Asian philosophy and religion, particularly Mahāyāna Buddhism. In these lectures, he applies the metaphor of the Platonic Cave to investigate Hegelian and Husserlian approaches to knowledge. Though he was a leading Hegel and Husserl scholar, his reading of these two philosophers is strongly influenced by Mahāyāna Buddhism, resulting in a unique mystical interpretation of these two philosophers. Revisiting Findlay’s writings is significant for two reasons; firstly, he investigated Buddhism prior to the Asian religions being included in Religious Studies departments’ purview in South African universities, and secondly, his interpretation of two prominent Western philosophers along Buddhist lines provides an early attempt at decolonising the predominance of Western philosophical views of knowledge.Contribution: This contribution forms part of a larger collection of essays investigating philosophical works that have had a significant impact on the study of religion. This contribution investigates the Buddhist influence on J.N. Findlay’s philosophical readings of Husserl and Hegel.